Associations of residential green space with internalizing and externalizing behavior in early childhood - Marnie F. Hazlehurst; Anjum Hajat; Pooja S. Tandon; Adam A. Szpiro; Joel D. Kaufman; Frances A. Tylavsky; Marion E. Hare; Sheela Sathyanarayana; Christine T. Loftus; Kaja Z. LeWinn; Nicole R. Bush; Catherine J. Karr (BMC, 2024)
Abstract Background Green space exposures may promote child mental health and well-being across multiple domains and stages of development. The aim of this study was to investigate associations between residential green space exposures and child mental and behavioral health at age 4-6 years. Methods Children's internalizing and externalizing behaviors in the Conditions Affecting Neurocognitive Development and Learning in Early Childhood (CANDLE) cohort in Shelby County, Tennessee, were parent-reported on the Child Behavior Checklist (CBCL). We examined three exposures-residential surrounding greenness calculated as the Normalized Difference Vegetation Index (NDVI), tree cover, and park proximity-averaged across the residential history for the year prior to outcome assessment. Linear regression models were adjusted for individual, household, and neighborhood-level confounders across multiple domains. Effect modification by neighborhood socioeconomic conditions was explored using multiplicative interaction terms. Results Children were on average 4.2 years (range 3.8-6.0) at outcome assessment. Among CANDLE mothers, 65% self-identified as Black, 29% as White, and 6% as another or multiple races; 41% had at least a college degree. Higher residential surrounding greenness was associated with lower internalizing behavior scores (-0.66 per 0.1 unit higher NDVI; 95% CI: -1.26, -0.07) in fully-adjusted models. The association between tree cover and internalizing behavior was in the hypothesized direction but confidence intervals included the null (-0.29 per 10% higher tree cover; 95% CI: -0.62, 0.04). No associations were observed between park proximity and internalizing behavior. We did not find any associations with externalizing behaviors or the attention problems subscale. Estimates were larger in neighborhoods with lower socioeconomic opportunity, but interaction terms were not statistically significant. Conclusions Our findings add to the accumulating evidence of the importance of residential green space for the prevention of internalizing problems among young children. This research suggests the prioritization of urban green spaces as a resource for child mental health.